Situation-bound utterances in Chinese. (17th November 2015) - Kecskes, Istvan
Abstract : This article argues that, when analysing formulaic language use in Chinese, besides the three main groups, proverbs (yànyǔ 谚语), idioms (chéngyǔ 成语), and guànyòngyǔ 惯用语 compounds, we need to distinguish and pay special attention to a fourth category: situation-bound utterances (qíngjìng zhuānyòngyǔ 情境专用 语). Situation-bound utterances (SBUs) constitute a unique group within idiomatic expressions because their use is tied to particular situations. SBUs fulfil social needs in conversation. People know that if they use these prefabricated expressions they are safe: nobody will misunderstand them because these phrases usually mean the same to most speakers in a speech community. The article aims to introduce SBUs as a separate category among Chinese formulaic expressions, discuss its relationship to yànyǔ, chéngyǔ, and guànyòngyǔ compounds, explain why it is important to handle it as a separate lexical category, and highlight the unique nature and use of SBUs. However, it is not the goal of the article to give a full and detailed description of the new category, which will need further research.